Brisingr, or, The Seven Promises of Eragon Shadeslayer and Saphira Bjartskular - Paolini, Christopher (New York : Alfred A. Knopf, 2008)
Presents the further adventures of Eragon and his dragon Saphira as they continue to aid the Varden in the struggle against the evil king, Galbatorix.
Keywords: Fiction; Dragons -- Fiction